ARABIC WRITING IN II-VII CENTURIES AND ITS REFLECTION IN THE QUR'AN BOOK (Academicia Globe: Inderscience Research, 2023)
Scholars argue that the Arabic script originated from the Nabataean script, based on several ancient inscriptions now known. Through these writings, it is possible to study the way in which the Nabatean script changed to the Arabic script and the script used to write the Holy Qur'an at the beginning of Islam. In this regard, it is necessary to get acquainted with the three most important scriptures. Two of them belong to the pre-Islamic centuries, and the third one was written in the first Hijri century. In the article, they are studied on the basis of historical tradition, and it is shown how their spelling features were reflected Uthman manuscripts.